Communication policy and the "double movement" - Ashley, Seth (Javnost (Ljubljana), 2014)
Karl Polanyi's concept of a "double movement" has been used to describe the protectionist measures taken by governments to mitigate damage caused by the expansion of markets. Through a lens of political economy and historical institutionalism, this article uses Polanyi's framework to examine competing notions of the public interest as exemplified by the socially constructed nature of American and British broadcasting and the legitimating discourse that produced divergent outcomes. A historical analysis points to a decline of the double movement in communication policy, particularly in the U.S., and lends support to calls for noncommercial, public media structures and increased regulation of communication industries.
Keywords: mass media; množični mediji; javnost; javna sfera; javni interes; konkurenca; trg; svobodna trgovina; država; state; politics; politika